A Review of Research on Grove Mountains CM-Type Chondrites - Wenjie Shen; Zhipeng Liang; Tianxiang Zou; Zhijun Yang; Weisheng Hou; Meng Zhou; Jialin Gong (Minerals, 2022)
CM chondrite is the most important carbonaceous chondrite containing abundant Ca, Al-rich inclusions (CAIs) and other interesting objects, which probably experienced early condensation processes in the Solar Nebula environment and later alteration in parent body surroundings. Thus, it is a vital raw material to explore in the formation and evolution of the early Solar System. Grove Mountains (GRV) CM chondrites have been collected from Antarctica by Chinese Antarctic Research Expedition (CARE) for nearly 20 years. In this paper, we review the study of GRV CM chondrites. In total, there are eight CM chondrites named Grove Mountains officially approved by the Meteoritical Society. Petrology and mineral, matrix, CAIs, metal and sulfide in GRV CM chondrites are carefully reviewed. All the meteorites have similar characteristics with a dominant component of matrix. Phyllosilicate minerals generally developed in the matrix. The different altered mineral assemblages, contents and chemical compositions show that these chondrites underwent varying degrees of aqueous alteration, of which GRV 020005 is the most heavily altered CM chondrite. GRV 020025 is the second heaviest of the CM samples with the most extensive studies among these chondrites. It contains abundant CAIs and amoeboid olivine aggregates (AOAs). The modal content is about 1.0 vol% for CAIs. The findings of some new types of CAIs (such as hibonite-rich and spinel-pyroxene inclusions with forsterite-rich accretionary rims), AOAs and a complex, fine-grained P-bearing sulfide phase enrich the study of GRV 020025.